Calcium thin film growth on polyfluorenes: Interface structure and energetics - Sharp, J. C.; Feng, X. F.; Farrner, J. A.; Guo, Y. X.; Bebensee, Fabian; Baricuatro, J. H.; Zillner, Elisabeth; Zhu, J. F.; Steinrück, Hans-Peter; Gottfried, Michael; Campbell, C. T. (Journal of Physical Chemistry C, 2014)
The adsorption of Ca vapor on two polyfluorenes, poly(9,9-di-n-hexyl-2,7- fluorene) (PDHF) and poly(9,9-di-n-hexyl-2,7-fluorene vinylene) (PDHFV), has been studied by adsorption microcalorimetry, low-energy He ion scattering spectroscopy (LEIS), and ultraviolet and X-ray photoelectron spectroscopies (UPS and XPS) at surface temperatures between 130 and ∼400 K. At 300 K, the initial heat of adsorption of Ca on PDHF is 250 kJ/mol and on PDHFV is 315 kJ/mol. We ascribe this initial heat to Ca reacting with impurities or defects in the polymers. The heat of adsorption for both polymers decreases nearly exponentially to the sublimation enthalpy of bulk Ca solid (178 kJ/mol) by 0.75 ML. The observed behavior is attributed to the increasing probability of Ca finding and adding to solid three-dimensional Ca islands which nucleate and grow on the polymer surface and eventually grow into a continuous solid Ca film on top of the polymer. LEIS, which shows only a slow increase of the signals related to solid Ca, supports this model. Incoming Ca atoms are subject to a kinetic competition between diffusing into the polymer to react with subsurface defects or impurities versus adding to the three-dimensional Ca clusters on the surface. For studies done at 140 K, a similar behavior is observed, with the heat of adsorption starting lower and decreasing more quickly to the heat of sublimation, already by 0.1 ML Ca coverage. This behavior, along with the quicker growth of Ca on the surface of the polymer, is attributed to the slower diffusion of Ca adatoms to subsurface defects/impurities at 140 K than at 300 K. The opposite effect is observed when studied at 400 K. Calcium induces a downward band bending and work function decrease on both polymers, consistent with transfer of electrons from Ca to the polymers. © 2014 American Chemical Society.